Nilai-Nilai Pendidikan Islam dalam Kiprah Ratu Sinuhun Menjaga Kehormatan Perempuan - Laila Rahmi Hasanah; Ismarani Junia Putri; Latifatuz Zahra; Abu Mansur; Nurlaila (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2026)
This study is motivated by the need to understand Islamic educational values within the Undang-Undang Simbur Cahaya authored by Ratu Sinuhun, particularly in safeguarding women’s dignity amid contemporary moral challenges. The research aims to describe and analyze these values as the foundation of Islamic character education. This library research employs a qualitative descriptive approach. The population consists of literature related to the Undang-Undang Simbur Cahaya and Ratu Sinuhun’s role, with purposive sampling. The main instrument is documentation and an analysis guideline, with data analyzed through content and descriptive analysis techniques. The findings confirm that the Undang-Undang Simbur Cahaya embodies values of faith, respect for human existence, responsible freedom, and social responsibility in preserving women’s dignity. The conclusion highlights that these values are highly relevant and suitable for integration into contemporary Islamic education to build a humane and contextual character.